Effect of Sc and Er additions on superplastic ductilities in Al-Mg-Mn-Zr alloy - Duan, Yu-lu; Qian, Jian; Xiao, Dan; Cui, Xue-min; Xu, Guo-fu (Journal of Central South University, 2016)
The superplasticity of Al-6Mg-0.4Mn-0.25Sc-0.12Zr and Al-6Mg-0.4Mn-0.25Er-0.12Zr (mass fraction, %) alloys sheet was investigated, and the effect of Sc and Er was discussed. The results show that the superplastic ductilities of Al-Mg-Mn-Sc-Zr alloy was higher than that of Al-Mg-Mn-Er-Zr alloy at a wide temperature range of 400-540 °C and high strain rate range of 1.67×10 -4 -1.67×10 -1 s -1 . A maximum elongation 673% is obtained at 520 °C and 1.67×10 -3 s -1 in the Sc-containing alloy; while the Er-containing alloy only gets a maximum elongation 253% at 520 °C and 1.67×10 -3 s -1 . Moreover, the average stress exponent of Sc-containing alloy is about 2.84, which is smaller than that of Er-containing alloy (3.64). Besides, the activation energies of the Sc-containing and Er-containing alloy are 84.8 kJ/mol and 87.2 kJ/mol, respectively. It is indicated that grain boundary sliding is the dominant mechanism during tensile deformation. According to microstructure examination, the better superplasticity of Sc-containing alloy may be attributed to the presence of Al 3 (Sc, Zr) dispersoids, which can inhibit recrystallization and grain growth effectively.